(untitled) (Journal of Hama University, 2020)
This research aimed to test the price efficiency of the Damascus Securities Exchange (DSE) and to evaluate the ability of the market index to reflect the nature of the price movements of the listed companies’ shares. The research was based on survey of closing prices time series during the period (from 1/8/2018 to 30/6/ 2019) after excluding public holidays and closing days, a set of tests was used to achieve the objectives of the research, including parametric and non- parametric tests such as (Run Test – Autocorrelation test - Unit Root test - descriptive statistics). The research pointed to main conclusion that the DSE is not efficient in its weak form, and that judging the efficiency of the DSE did not differ according to the test methods used, whether it is Run Test, Autocorrelation test, or Unit Root test or even the results of the descriptive statistics of shares’ closing prices, as they all confirmed that the stock prices in DSE does not move randomly and that there is a strong Autocorrelation between the daily shares’ closing prices of listed companies, in addition to that, the time series of closing prices for most companies (15 companies) were stationary without any differences and the rest of the companies (9 companies) where the time series of closing prices were stationary at the first difference only, including the time series of DSE index where it was also stationary without any differences. It is also clear that the DSE index reflects the nature of stock price movements of all listed companies. There is no difference between the results of the statistical tests applied to the shares of companies listed on the DSE and the statistical tests applied to the DSE index.